2017
DOI: 10.1021/acssuschemeng.7b02147
|View full text |Cite
|
Sign up to set email alerts
|

Techno-economic Assessment for Integrating Biosorption into Rare Earth Recovery Process

Abstract: The current uncertainty in the global supply of rare earth elements (REEs) necessitates the development of novel extraction technologies that utilize a variety of REE source materials. Herein, we examined the techno-economic performance of integrating a biosorption approach into a large-scale process for producing salable total rare earth oxides (TREOs) from various feedstocks. An airlift bioreactor is proposed to carry out a biosorption process mediated by bioengineered rare earth-adsorbing bacteria. Techno-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 36 publications
0
38
0
Order By: Relevance
“…However, many countries are now facing REE supply uncertainties due to the near monopolistic supply from China (e.g., ∼95% of rare-earth oxide (REO) production). Moreover, the recent COVID-19 pandemic has created a global supply and demand imbalance for REE compounds, highlighting the importance of source diversification . This supply disruption has exposed the United States and other countries vulnerable to rare-earth resources and motivated them to delve into other means of extracting the critical materials from a variety of REE-containing materials. …”
Section: Introductionmentioning
confidence: 99%
“…However, many countries are now facing REE supply uncertainties due to the near monopolistic supply from China (e.g., ∼95% of rare-earth oxide (REO) production). Moreover, the recent COVID-19 pandemic has created a global supply and demand imbalance for REE compounds, highlighting the importance of source diversification . This supply disruption has exposed the United States and other countries vulnerable to rare-earth resources and motivated them to delve into other means of extracting the critical materials from a variety of REE-containing materials. …”
Section: Introductionmentioning
confidence: 99%
“…19 Although they have relatively low REE concentrations, geofluids are abundant and have the advantage of requiring minimal pretreatment prior to REE extraction, unlike solid feedstocks such as ores and ion adsorption clays, for which chemical leaching is generally required. 19,25,31 Herein, we systematically examined the effects of TDS, competing metals, pH, and temperature on REE adsorption efficiency and selectivity. Results define the geochemical conditions that are amenable to REE biosorption, information that is key to the future development of a high-performance biosorption technology for REE recovery from geofluids.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To our knowledge, robust TEA and LCA analyses for contaminant removal and/or recovery from water or wastewater using cell-free, protein-based biosorbents have not been conducted. However, two TEAs focused on the use of intact bacterial cells for sorption and recovery of rare earth elements from industrial byproducts identified specific applications that were economically viable ( Alipanah et al., 2020 ; Jin et al., 2017 ). Both studies incorporated immobilization and reuse of the whole-cell biosorbents, which was critical for economic and environmental performance.…”
Section: Evaluating the Economic Feasibility Of Biocatalysis And Biosorptionmentioning
confidence: 99%
“…Both studies incorporated immobilization and reuse of the whole-cell biosorbents, which was critical for economic and environmental performance. Considering stability and matrix complexity, the surface-expressed peptide tags on these cells were active in a range of complex matrices, including acid leachate and geothermal brine ( Jin et al., 2017 ).…”
Section: Evaluating the Economic Feasibility Of Biocatalysis And Biosorptionmentioning
confidence: 99%